Deficiency of acyl-CoA synthetase 5 is associated with a severe and treatable failure to thrive of neonatal onset - Al-Thihli, Khalid; Afting, Cassian; Al-Hashmi, Nadia; Mohammed, Mohammed; Sliwinski, Svenja Christin; Al Shibli, Naema; Al-Said, Khoula; Al-Kasbi, Ghalia; Al-Kharusi, Khalsa; Merle, Uta; Füllekrug, Joachim; Al-Maawali, Almundher (Clinical genetics, 2021)
Failure to thrive (FTT) causes significant morbidity, often without clear etiologies. Six individuals of a large consanguineous family presented in the neonatal period with recurrent vomiting and diarrhea, leading to severe FTT. Standard diagnostic work up did not ascertain an etiology. Autozygosity mapping and whole exome sequencing identified homozygosity for a novel genetic variant of the long chain fatty acyl-CoA synthetase 5 (ACSL5) shared among the affected individuals (NM_203379.1:c.1358C>A:p.(Thr453Lys)). Autosomal recessive genotype-phenotype segregation was confirmed by Sanger sequencing. Functional in vitro analysis of the ACSL5 variant by immunofluorescence, western blotting and enzyme assay suggested that Thr453Lys is a loss-of-function mutation without any remaining activity. ACSL5 belongs to an essential enzyme family required for lipid metabolism and is known to contribute the major activity in the mouse intestine. Based on the function of ACSL5 in intestinal long chain fatty acid metabolism and the gastroenterological symptoms, affected individuals were treated with total parenteral nutrition or medium-chain triglyceride-based formula restricted in long-chain triglycerides. The patients responded well and follow up suggests that treatment is only required during early life.